2022
DOI: 10.1111/cfs.12946
|View full text |Cite
|
Sign up to set email alerts
|

Interventions in child welfare: A Swedish inventory

Abstract: In Swedish child welfare, there are no mandatory guidelines on what interventions to use. Local authorities are able to set their own criteria for implementing or designing interventions. We carried out a survey to identify interventions in use in Children's Social Services and Child and Adolescent Psychiatric Care in Sweden. A total of 102 interventions were stated to have been in use, with between 31 and 45 different interventions for each of the four different child welfare populations. Of the 102 intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…Cultural fit is key to intervention success [ 57 , 58 ] but there remains debate in the extant literature on whether this fit should be managed through the cultural adaptation of existing interventions to new context or whether fidelity should be seen as paramount [ 59 ]. In addition, a large proportion of interventions are developed in the settings in which they will be used [ 59 , 60 ]. The current research may be able to contribute to this scholarship in that we test the intervention My Choice–My Way!…”
Section: Discussionmentioning
confidence: 99%
“…Cultural fit is key to intervention success [ 57 , 58 ] but there remains debate in the extant literature on whether this fit should be managed through the cultural adaptation of existing interventions to new context or whether fidelity should be seen as paramount [ 59 ]. In addition, a large proportion of interventions are developed in the settings in which they will be used [ 59 , 60 ]. The current research may be able to contribute to this scholarship in that we test the intervention My Choice–My Way!…”
Section: Discussionmentioning
confidence: 99%
“…Our findings about parents' positive experience of learning new parenting strategies are perhaps the least novel given the plethora of research demonstrating the appropriateness and effectiveness of these strategies (Dishion, Forgatch, Chamberlain & Pelham, 2016; Leijten, Melendez‐Torres & Gardner, 2022). Previous research in Sweden has demonstrated that parents of adolescents report positive outcomes associated with a Swedish developed program based in PMTO (Alfredsson, Thorvaldsson, Axberg & Broberg, 2018; Bergström et al ., 2022). Our findings extend previous research in the context of individualized delivery of parent support via FCU with EDP.…”
Section: Discussionmentioning
confidence: 99%
“…The EDP is a manual-based parent training curriculum adapted from the Oregon model of Parent Management Training (PMTO; Forgatch & Patterson, 2010) to be delivered individually rather than in a group format. Many parenting programs currently offered in a Swedish context are based in PMTO, and like those, the EDP focuses on reducing child defiance by teaching parenting strategies that encourage and reinforce positive behavior (Bergstr€ om, Sundell, Olsson, Leander & Astr€ om, 2022). Three areas of parenting practices are covered in EDP: (1) positive behavior support; (2) monitoring and limitsetting; and (3) relationship-building.…”
Section: Family Check-upmentioning
confidence: 99%
“…In research-based interventions, there is usually a manual containing relevant program theory. In interventions of a more generic nature and unspecific origin (e.g., counseling, network therapy), there is normally no manual available for consultation (Bergström et al, 2022). This in itself may be a warning, since one can expect increased heterogeneity in the population for which the intervention is intended, as well as in the content of the intervention.…”
Section: Program Theorymentioning
confidence: 99%
“…There are hundreds of social work interventions (methods, treatments, and services) in use, but few have been scientifically evaluated. An inventory of the child welfare services currently in use in Sweden identified 102 different interventions, of which nine were well-supported by research, according to the California Evidence-Based Clearinghouse, which means that at least two rigorous randomized controlled trials (RCTs) found the interventions to be superior to an appropriate comparison (Bergström et al, 2022). A gap between research and practice can mean that clients do not receive services that are effective and therefore may suffer from poorer outcomes.…”
mentioning
confidence: 99%